Lower calcium and iron intake in adolescent handball players: is a new trend emerging? - Sziraki, Zs.; Nyakas, Cs.; Szmodis, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: An adequately composed diet plays a particularly important role in the proper development and sports performance of adolescent athletes. The purpose of the study was to determine whether young female handball players consume adequate amounts of nutrients, especially calcium and iron. METHODS: 32 elite youth female athletes (age 15.34 ± 1.89 y, body height 166.7 ± 5.81 cm, body weight 60.61 ± 9.47 kg, BMI 21.81 kg/m2) were included in our cross-sectional study (2020-2021). Anthropometric measurements (Inbody 770, skinfold measurements) were performed on the athletes, and they also filled out a 3-Day Food Record (Analysis software: Nutricomp DietCAD 5.0). The statistical analysis was performed with the JAMOVI 2.4.14 program. The significance level was p